ICES zooplankton methodology manual - Harris, Roger (Roger P.) (Academic, 2000)
The term "zooplankton" describes the community of floating, often microscopic, animals that inhabit aquatic environments. Being near the base of the food chain, they serve as food for larger animals, such as fish. The ICES (International Council for the Exploration of the Sea) Zooplankton Methodology Manual provides comprehensive coverage of modern techniques in zooplankton ecology written by a group of international experts. Chapters include sampling, acoustic and optical methods, estimation of feeding, growth, reproduction and metabolism, and up-to-date treatment of population genetics and modeling. This book will be a key reference work for marine scientists throughout the world. Key features * Sampling and experimental design * Collecting zooplankton * Techniques for assessing biomass and abundance * Protozooplankton enumeration and biomass estimation * New optical and acoustic techniques for estimating zooplankton biomass and abundance * Methods for measuring zooplankton feeding, growth, reproduction and metabolism * Population genetic analysis of zooplankton * Modelling zooplankton dynamics This unique and comprehensive reference work will be essential reading for marine and freshwater research scientists and graduates entering the field